2020
DOI: 10.1007/s41782-020-00105-5
|View full text |Cite
|
Sign up to set email alerts
|

The Monday Effect Revisited: A Diary and Sleep Actigraphy Study

Abstract: Purpose Accidents are more likely to occur during the morning hours of Mondays (Monday effect). This might be due to a higher level of cognitive failure on Monday morning at work. Methods In a pilot actigraphy study across one working week, we explored this Monday effect and regressed daily self-reported workplace cognitive failure on weekdays (Monday versus other days), background social stressors at work, delayed sleep onset and sleep duration. Diary data were gathered from 40 full-time employees. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
(57 reference statements)
2
7
0
Order By: Relevance
“…Although there is substantial variance in sleep duration across workdays, our data did not reveal a relationship between daily sleep duration and workplace cognitive failures. This is consistent with recent actigraphy studies that emphasize the importance of sleeponset latency for cognitive functioning problems beyond sleep duration (Elfering et al, 2020;Kottwitz et al, 2019). Future studies might also examine the extent to which sleep duration can be compensated, for example, due to longer sleep on the weekend (Kubo et al, 2011), in order to maintain daily cognitive functioning.…”
Section: Additional Analysessupporting
confidence: 87%
See 2 more Smart Citations
“…Although there is substantial variance in sleep duration across workdays, our data did not reveal a relationship between daily sleep duration and workplace cognitive failures. This is consistent with recent actigraphy studies that emphasize the importance of sleeponset latency for cognitive functioning problems beyond sleep duration (Elfering et al, 2020;Kottwitz et al, 2019). Future studies might also examine the extent to which sleep duration can be compensated, for example, due to longer sleep on the weekend (Kubo et al, 2011), in order to maintain daily cognitive functioning.…”
Section: Additional Analysessupporting
confidence: 87%
“…As a result, the individual may be more prone cognitive failures at work (Brossoit et al, 2019;Wallace & Chen, 2005). This assumption was recently supported by actigraphy studies showing that sleep-onset latency predicts cognitive failure (Elfering et al, 2020) and problems concentrating (Kottwitz et al, 2019) at work.…”
Section: Cognitive Failures As a Consequence Of Impaired Sleepmentioning
confidence: 84%
See 1 more Smart Citation
“…Research has shown that high levels of MWL at work play a role in accidents at home [17], and the impact of the weekend can afect accidents at work [16]. Similarly, demands for mental efort in our home lives can lead to poor performance at work [33].…”
Section: Personal Cognitive Informaticsmentioning
confidence: 99%
“…The importance of sleep for performance and safety in the workplace has been widely recognised [58][59][60]. An important way of intervening in sleep habits is to improve sleep quality.…”
Section: Strengths and Limitationsmentioning
confidence: 99%